2021
DOI: 10.1007/s12350-019-01604-3
|View full text |Cite
|
Sign up to set email alerts
|

Perspective and future direction of intraventricular mechanical dyssynchrony assessment

Abstract: This editorial refers to the article published by Peix et al. 1 titled 'Value of intraventricular dyssynchrony assessment by gated-SPECT myocardial perfusion imaging in the management of heart failure patients undergoing cardiac resynchronization therapy (VISION-CRT)' on the Journal of Nuclear Cardiology. This study shows the importance of the current problem in cardiac resynchronization therapy (CRT). In this study, we observe multiple variables that can affect the CRT response in clinical practice 2 : patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Some proponents of LVD have suggested that a normal MPI should be reported only when LVD is also normal in addition to perfusion, thickening, and function. 16 While this may be reasonable in a population without HF, as LVD may provide additive value, its application from a prognostic standpoint alone among those with CAD and HF needs careful consideration. In these patients is LVD a result of ischemia or stunning from CAD or driven by HF?…”
mentioning
confidence: 99%
“…Some proponents of LVD have suggested that a normal MPI should be reported only when LVD is also normal in addition to perfusion, thickening, and function. 16 While this may be reasonable in a population without HF, as LVD may provide additive value, its application from a prognostic standpoint alone among those with CAD and HF needs careful consideration. In these patients is LVD a result of ischemia or stunning from CAD or driven by HF?…”
mentioning
confidence: 99%